2019
DOI: 10.3357/amhp.5237.2019
|View full text |Cite
|
Sign up to set email alerts
|

Capacity to Compensate for Central Hypovolemia and Effects of Menstrual Cycle Phases

Abstract: BACKGROUND: Tolerance to central hypovolemia is dictated by exhaustion of the physiological capacity to compensate called the compensatory reserve. Such physiological compromise can have detrimental impact on performance in aerospace environments as well as survival from hemorrhage on the battlefield. We induced central hypovolemia using progressively stepwise lower body negative pressure (LBNP) in women during various phases of the menstrual cycle to test the hypothesis that similar tolerance across all mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Rather, as an exploratory aim of the parent projects, we sought to identify whether there was an interaction between the menstrual cycle phase and the administered analgesic on the variables of interest. Third, previous studies have shown that MSNA is higher in the midluteal phase of the menstrual cycle (38,39); however, such responses do not alter tolerance to LBNP (40). In the present study, the phase of the menstrual cycle on the days the trials were performed was not controlled.…”
Section: Discussionmentioning
confidence: 95%
“…Rather, as an exploratory aim of the parent projects, we sought to identify whether there was an interaction between the menstrual cycle phase and the administered analgesic on the variables of interest. Third, previous studies have shown that MSNA is higher in the midluteal phase of the menstrual cycle (38,39); however, such responses do not alter tolerance to LBNP (40). In the present study, the phase of the menstrual cycle on the days the trials were performed was not controlled.…”
Section: Discussionmentioning
confidence: 95%
“…Participants were recruited via flyers and word of mouth from the general Colorado Springs area. Female subjects were not taking birth control medication and were tested 5 ± 3 days after the onset of menses in order to control for the potential influence of variations in sex hormone concentration throughout the menstrual cycle on neural and hemodynamic responses to orthostatic stress (Usselman et al, 2016), although recent evidence suggests that cardiovascular responses and tolerance to central hypovolemia are not affected by menstrual cycle phase (Convertino et al, 2019). For a detailed review of the effects of sex hormones and the menstrual cycle upon hemodynamic responses and time to presyncope, the reader is referred to Goswami et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…48 It is unlikely that this difference is attributed to sex hormones, as menstrual cycle phase was found to be unrelated to LBNP tolerance. 49
Fig. 3Defining the compensatory reserve.
…”
Section: The Compensatory Reserve As a Reflection Of Delivery Of Oxygenmentioning
confidence: 99%